PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS KARANGAN EKSPOSISI SISWA KELAS X SMA EKASAKTI PADANG - Zuraida Khairani; Dwi Mutia Chan; Najmi Hayati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
The purpose of this research. First, it describes the writing skills of exposition essays for class X students of SMA Negeri Ekasakti Padang before applying the Problem Based Learning (PBL) model assisted by media images. Second, it describes the exposition essay writing skills of class X SMA Ekasakti Padang after applying the Problem Based Learning (PBL) model assisted by media images. Third, analyzing the effect of Problem Based Learning (PBL) assisted by media images on the exposition essay writing skills of class X SMA Ekasakti Padang. This type of research is quantitative research. The results of data analysis and discussion are. First, the exposition writing skills of class X.2 SMA Ekasakti Padang before applying the Problem Based Learning (PBL) model assisted by media images were in the "Enough" qualification with an average score of 58. Second, the writing skills of class X.2 Ekasakti Padang exposition essays after applying the Problem Based Learning (PBL) model assisted by media images are in the "Good" qualification with an average score of 83. Third, there is the influence of the application of the Problem Based Learning (PBL) model assisted by media images on the exposition essay writing skills of class X.2 SMA Ekasakti Padang. The results of testing the hypothesis obtained tcount of 7.35 and ttable of 1.70 at P 0.95. So, the application of the Problem Based Learning (PBL) model assisted by media images has a significant effect on the exposition essay writing skills of class X.2 SMA Ekasakti Padang